Effects of Biogas Slurry Combined With Chemical Fertilizer on Soil Bacterial and Fungal Community Composition in a Paddy Field - Zhang, Hanlin; Li, Shuangxi; Zheng, Xianqing; Zhang, Juanqin; Bai, Naling; Zhang, Haiyun; Lv, Weiguang (Frontiers in Microbiology, 2021)
The application of biogas slurry and chemical fertilizer in paddy fields can be a practical method to reduce the environmental risk and utilize the nutrients of biogas slurry. The responses of bacterial and fungal communities to the application of biogas slurry and chemical fertilizer are important reflections of the quality of the ecological environment. In this study, based on a 3-year field experiment with different ratios of biogas slurry and chemical fertilizer (applying the same pure nitrogen amount), the Illumina MiSeq platform was used to investigate the bacterial and fungal community diversity and composition in paddy soil. Our results revealed that compared with the observations under regular chemical fertilization, on the basis of stable paddy yield, the application of biogas slurry combined with chemical fertilizer significantly enhanced the soil nutrient availability and bacterial community diversity and reduced the fungal community diversity. Dissolved organic carbon (DOC), DOC/SOC (soil organic carbon), available nitrogen (AN) and available phosphorus (AP) were positively correlated with the bacterial community diversity, but no soil property was significantly associated with the fungal community. The bacterial community was primarily driven by the application of biogas slurry combined with chemical fertilizer (40.78%), while the fungal community was almost equally affected by the addition of pure biogas slurry, chemical fertilizer and biogas slurry combined with chemical fertilizer (25.65–28.72%). Biogas slurry combined with chemical fertilizer significantly enriched Proteobacteria, Acidobacteria, Planctomycetes, Rokubacteria, and Ascomycota and depleted Chloroflexi, Bacteroidetes, Crenarchaeota, Basidiomycota, and Glomeromycota. The observation of the alteration of some bacteria- and fungus-specific taxa provides insights for the proper application of biogas slurry combined with chemical fertilizer, which has the potential to promote crop growth and inhibit pathogens.